Pengembangan Desa Menjadi Desa Tangguh Bencana (DESTANA) Melalui Kuliah Kerja Nyata Tematik di Negeri Tulehu - Sarabiti, Rinaldi E. S.; Botanri, Adnan Affan Akbar; Lekransy, Francois (EMPOWERMENT: Journal of Community Practice, 2024)
One of the most important approaches is the development of villages to become disaster-resilient villages. One of the strategies to improve community preparedness is to develop a Disaster Resilient Village (Destana). The purpose of the development of Destana is to increase the capacity of the community in dealing with and recovering from disasters. The method of implementing the State profile preparation program by Tulehu State Thematic KKN Students is carried out in a collaborative and multidisciplinary model. The implementation of this Community Service Activity is carried out by following 3 stages which include the planning stage, the preparation stage and the socialization and simulation stage. Data collection is carried out through observation, interviews, and documentation. Community service through Thematic KKN has a great influence on public awareness of the importance of having an understanding related to the willingness to face disasters both in terms of knowledge and equipment that must be prepared. Because in community service activities through the Thematic KKN program, it has a very positive effect on the community as well as school students to know their preparedness in dealing with the disaster. The implementation of socialization and simulation is a form of activity that seeks the State of Tulehu to be included in the category of ready to face disasters through a video that will be sent directly by the Tulehu State Thematic KKN Group to the Central Maluku BNPB.